Incidence, Risk Factors, and Outcome of Ventilator-Associated Pneumonia in an Intensive Care Unit - Parisa Delkash; Soheila Sadeghi; Seyed Amir Sheikholeslami; Mahmoud Dehghani-Ghorbi; Amir Behnam Kharazmi (Archives of Anesthesia and Critical Care)
Background: Ventilator-Associated Pneumonia (VAP) is one of the most common nosocomial infections that occurs after intubation in patients with mechanical ventilation. Methods: This cross-sectional descriptive study was conducted in a group of patients admitted to the ICU with a sample size of 120 patients. patients were visited daily at the beginning of admission to the ICU and the study began by considering the entry and exit criteria. To achieve the research objectives, researchers visited the ICI department daily and identified eligible patients. Also, in this study, the demographic profile form of the patients was designed, and their information was completed by the researchers according to the information in the patients' clinical records. The questions of the demographic profile form were completed using an interview with the patient's companion and a study of the patient's hospitalization records. The data from this study were entered into SPSS version 18 and analysed using chi-square, regression, Mann-Whitney and other statistical tests. Results: According to the findings, 120 patients admitted to the ICU were included in the study, of which 48.3% were male and 51.7% were female. The incidence of VAP in 24 patients (20%) was reported. most of the VAP Group patients were male with a rate of 70.8%, age group 70-80 years with a rate of 66.7%, a history of smoking with a rate of 100% and consciousness above 9 with a rate of 70.8%. Also, in patients with VAP, 91.7% of patients with cancer and 41.7% of patients with rheumatoid arthritis had comorbidities, which was significant compared to the No-VAP Group (P value<0.05). Conclusion: Given the high prevalence of VAP and its role in patient mortality, preventive interventions are recommended to reduce the incidence of VAP.